2019
DOI: 10.18632/aging.102291
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of LncRNA-XIST inhibited development of non-small cell lung cancer by activating miR-335/SOD2/ROS signal pathway mediated pyroptotic cell death

Abstract: LncRNA-XIST participated in the regulation of Non-small cell lung cancer (NSCLC) progression, but the underlying mechanisms are still unclear. This study showed that LncRNA-XIST aberrantly overexpressed in either NSCLC tissues or cell lines comparing to their paired control groups. Knock-down of LncRNA-XIST promoted NSCLC cell apoptosis and inhibited cell proliferation, which were reversed by synergistically treating cells with pyroptosis inhibitor Necrosulfonamide (NSA). In addition, knock-down of LncRNA-XIST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 32 publications
2
130
0
1
Order By: Relevance
“…Thus, inhibiting LncRNA-XIST may contribute to the treatment of NSCLC patients. Subsequent experiments found that knocking down LncRNA-XIST led to pyroptosis by activating the miR-335/SOD2/ROS/ NLRP3 signal pathway (60). In another research, downregulation of LncRNA-XIST was demonstrated to relieve its suppression of Smad2 nuclear translocation, subsequently triggering transcriptional activation of P53 and NLRP3.…”
Section: Lung Cancermentioning
confidence: 97%
“…Thus, inhibiting LncRNA-XIST may contribute to the treatment of NSCLC patients. Subsequent experiments found that knocking down LncRNA-XIST led to pyroptosis by activating the miR-335/SOD2/ROS/ NLRP3 signal pathway (60). In another research, downregulation of LncRNA-XIST was demonstrated to relieve its suppression of Smad2 nuclear translocation, subsequently triggering transcriptional activation of P53 and NLRP3.…”
Section: Lung Cancermentioning
confidence: 97%
“…For instance, lncRNA XIST has been reported to regulate cell proliferation in non-small cell lung cancer by modulating miR-186-5p and miR-335/SOD2/ROS signaling pathways. 8,9 Moreover, lncRNA XIST has been shown to target miR-194-5p and miR-139-5p to regulate growth of hepatocellular carcinoma cells. 12,34 Further, lncRNA XIST has been demonstrated to promote proliferation of pancreatic cancer cells by acting as a sponge for miR-429 and miR-133a.…”
Section: Discussionmentioning
confidence: 99%
“…To normalize the values, each firefly luciferase value was divided by the value for renilla luciferase in the same well. 9,29 Tumor Xenograft Model…”
Section: Luciferase Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increasing evidence has revealed the multiple functions of lncRNAs on cell fate regulation, especially on tumorigenesis [11]. For example, lncRNA-MALAT1 [12,13] and lncRNA-XIST [14,15] have been elucidated to regulate the proliferation, invasion, and migration of NSCLC. Still, there have been a large amount of lncRNAs whose effects on NSCLC tumorigenesis have not been clearly identified.…”
Section: Introductionmentioning
confidence: 99%